Stray Care: A Platform for Managing Issues of Stray Animals - Haziqah Nazurah, Zawawi (Universiti Malaysia Sarawak, (UNIMAS), 2023)
Animals can be humans’ best friends as they become pets. It is assumed that their welfare including food, shelter and health are being taken care of by their owners. However, we cannot assume the same for the stray animals on the street. Stray animals may continue to breed and populate as they are unneutered. Furthermore, they may also carry dangerous diseases such as rabies which is known in Sarawak. In addition, we cannot rely solely on animal shelters to accommodate all stray animals because shelters are meant to provide room for more desperate animals. Moreover, some pet owners abandoned their pets because of the financial struggle to support their pets’ welfare after the Movement Control Order (MCO). These animals would have accidental death, illness and so on because they lack basic survival skills. Thus, the number of stray animals is increasing due to these issues. To mitigate this problem, an online platform to manage issues of stray animals called Stray Care is proposed. The expected outcome of this project is to facilitate the public to rescue and save stray animals. The users of this platform will be able to add, view and share the information of stray animals such as location and health. As a result, users will be able to adopt the animals, give them a second chance for a better life and reduce the number of stray animals. The survey results from 10 testers indicate that the majority agree that Stray Care is capable of storing and retrieving records on stray animals and their adoption status, as well as providing effective education modules for users to acquire knowledge about animals. Additionally, the survey respondents found the application to be useful to help in searching and adopting stray animals.